ICT-Related Intangibles and Organizational Innovation: Indicators for Improving Connectedness and Flexibility - Koskinen, Minna; Luomala, Joni; Maaranen, Petri (Human Technology, 2012)
In this paper we address the role of ICT-related intangible assets in organizational innovation. We focus on two important innovation enablers: first, connectedness, the ability of individuals to create and maintain connections to each other; and second, organizational flexibility to adapt to changing needs. For connectedness and flexibility, an agile ICT infrastructure and information management services are needed. Through a Delphi study, we identified several factors hindering organizational innovation, and formulated a set of indicators and related metrics for improvement. We conclude that it is necessary to consider ICT-related factors when organizations pursue improving their innovativeness. However, ICT solutions do not lead to organizational innovativeness independent of other organizational factors and people. If the organization is well-functioning, suitable ICT solutions can provide important added value for its innovation activities.